An In Vitro Model to Investigate the Role of Helicobacter Pylori in Type 2 Diabetes, Obesity, Alzheimer’s Disease and Cardiometabolic Disease - Cuomo, Paola (Int J Mol Sci, 2020)
Helicobacter pylori (Hp) is a Gram-negative bacterium colonizing the human stomach. Nuclear Magnetic Resonance (NMR) analysis of intracellular human gastric carcinoma cells (MKN-28) incubated with the Hp cell filtrate (Hpcf) displays high levels of amino acids, including the branched chain amino acids (BCAA) isoleucine, leucine, and valine. Polymerase chain reaction (PCR) Array Technology shows upregulation of mammalian Target Of Rapamycin Complex 1 (mTORC1), inflammation, and mitochondrial dysfunction. The review of literature indicates that these traits are common to type 2 diabetes, obesity, Alzheimer’s diseases, and cardiometabolic disease. Here, we demonstrate how Hp may modulate these traits. Hp induces high levels of amino acids, which, in turn, activate mTORC1, which is the complex regulating the metabolism of the host. A high level of BCAA and upregulation of mTORC1 are, thus, directly regulated by Hp. Furthermore, Hp modulates inflammation, which is functional to the persistence of chronic infection and the asymptomatic state of the host. Finally, in order to induce autophagy and sustain bacterial colonization of gastric mucosa, the Hp toxin VacA localizes within mitochondria, causing fragmentation of these organelles, depletion of ATP, and oxidative stress. In conclusion, our in vitro disease model replicates the main traits common to the above four diseases and shows how Hp may potentially manipulate them.